2021
DOI: 10.3389/fmed.2021.615342
|View full text |Cite
|
Sign up to set email alerts
|

Successful HCV Therapy Reduces Liver Disease Severity and Inflammation Biomarkers in HIV/HCV-Coinfected Patients With Advanced Cirrhosis: A Cohort Study

Abstract: Background: Eradication of hepatitis C virus (HCV) promotes an improvement in liver disease and the deactivation of the immune system. Here, we aimed to evaluate the changes in liver disease scores and plasma biomarkers following HCV clearance with direct-acting antivirals (DAAs) in HIV-infected patients with advanced HCV-related cirrhosis.Methods: We performed an observational study of 50 patients with advanced cirrhosis who received DAAs therapy. Variables were assessed at baseline and 48 weeks after HCV tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
1
8
0
2
Order By: Relevance
“…Regarding HIV/HCV-coinfected patients, there are limited data on their status following DAA therapy. However, some of our findings are similar to those described in previous studies showing improved liver function ( 56 61 ) and a decrease in plasma chemokine levels (CXCL10, CCL2, and CXCL8) ( 45 , 62 66 ). Chemokines attract leucocytes to the liver, promoting cirrhosis and the appearance of LRE ( 67 ), and they are surrogate markers of liver inflammation ( 68 ).…”
Section: Discussionsupporting
confidence: 92%
“…Regarding HIV/HCV-coinfected patients, there are limited data on their status following DAA therapy. However, some of our findings are similar to those described in previous studies showing improved liver function ( 56 61 ) and a decrease in plasma chemokine levels (CXCL10, CCL2, and CXCL8) ( 45 , 62 66 ). Chemokines attract leucocytes to the liver, promoting cirrhosis and the appearance of LRE ( 67 ), and they are surrogate markers of liver inflammation ( 68 ).…”
Section: Discussionsupporting
confidence: 92%
“…The introduction of both HAART for HIV-1 infection and DAAs against HCV has significantly improved the prognosis of HIV/HCV co-infected patients with ESLD [ 1 , 2 , 3 , 7 , 8 , 9 , 10 , 11 ]. However, reinfection of graft is practically inevitable in HCV positive transplanted patients and the presence of co-infection with HIV makes the evolution towards fibrosis more rapid [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of direct-acting antiviral agents (DAAs) against HCV has significantly improved the prognosis of HCV/HIV co-infected patients undergoing liver transplantation for end stage liver disease (ESLD) [ 7 , 8 , 9 , 10 , 11 ]. However, recent studies have suggested that DAA-mediated HCV eradication could represent an impediment to HIV reservoir elimination in coinfected patients [ 4 , 12 ], and that DAA treatment does not completely normalize immune and liver functions as well as the risk of hepatocellular carcinoma development [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, whether the improved clinical outcomes of DAA coincide with better immunological outcomes is still unclear. There is good evidence that SVR reduces the rate of progression to cirrhosis and lowers levels of soluble inflammatory biomarkers in cirrhotics [61], an indication that HCV clearance is directly responsible for improvement in both liver tissue integrity and hepatic immune homeostatic function, with far reaching effects on systemic immunity.…”
Section: Liver Cirrhosis Is Associated With Altered Immune Homeostasismentioning
confidence: 99%